Good Faith sebagai Penentu dalam Pemenuhan Unsur Tindak Pidana Penipuan dan Wanprestasi dalam Putusan Perkara Nomor 38/Pdt.G/2024/PN Slw - Perdana, Mohammad Ardhi; Jadidah, Fikrotul (PT Elaborium Elevasi Indonesia, 2025)
This study aims to review and analyze the normative legal aspects within the perspective of civil law in Indonesia, including legal considerations and the application of default (wanprestasi) in debt settlement agreements in the decision of the Slawi District Court Number 38/Pdt.G/2024/PN Slw. This is a normative legal research with data collection techniques using secondary data sources. The data collection method is through literature study, and the analysis is conducted using qualitative analysis. The results of this research include references to the Indonesian Criminal Procedure Code (KUHAP), the Indonesian Penal Code (KUHP), and the Indonesian Civil Code. The focus of this research is on the application of good faith in determining the decision between fraud and default. The findings indicate that in the decision Number 38/Pdt.G/2024/PN Slw, it was categorized as default (wanprestasi) because there was no bad faith in its resolution